Answer to part A: 11w^2+7z^2
Answer to part B: 14w^2+9w
=================================================
Step-by-step explanation:
For part A, the expression 4w^2+7w^2+7z^2 has one pair of like terms. That pair is 4w^2 and 7w^2 which combine to 11w^2. You add the coefficients to get 4+7 = 11, then tack w^2 onto everything to say 4w^2+7w^2 = 11w^2
We cannot combine 11w^2 and 7z^2 as they aren't like terms. So we leave it as 11w^2+7z^2
--------------------
In part B, the like terms are 15w and -9w. They combine to 15w-9w = 6w. You can think of it like 15-9 = 6 then stick a 'w' to each term. We cannot combine the w^2 term with the w terms.